Expression of rotavirus VP6 protein: a comparison amongst Escherichia coli, Pichia pastoris and Hansenula polymorpha. Issue 2 (14th January 2016) - Bredell, Helba; Smith, Jacques J.; Prins, Willem A.; Görgens, Johann F.; van Zyl, Willem H.
Abstract : During this study. we successfully expressed a codon-optimized gene for rotavirus VP6 protein intracellularly in two methylotrophic yeasts, Pichia pastoris and Hansenula polymorpha, during methanol induction. Expressions were performed in shake flasks and subsequently scaled-up to 1.3 L bioreactors. The yields obtained in the yeasts were compared with that observed in Escherichia coli . Despite producing the lowest biomass levels of all the expression systems in shake flasks, the highest VP6 concentration was obtained with E. coli . In shake flasks, P. pastoris yielded higher volumetric levels of VP6 than H. polymorpha, but specific production of VP6 was approximately similar in both yeasts. In the controlled environment of bioreactors, yeast strains attained typical high cell densities, but also increased VP6 production compared to all shake flask cultures. Unlike in shake flask expressions, H. polymorpha outperformed both P. pastoris as well as E. coli during bioreactor cultivation. VP6 production was in all three expression systems growth-associated. In contrast to yeast expressions, bacterial expressed VP6 protein was found to be insoluble upon analysis. This is the first report of VP6 expressed in methylotrophic yeast and holds the promise for the inexpensive production of VP6 as a possible vaccine candidate or drug delivery mechanism. Abstract : The rotavirus VP6 protein was successfully produced in Pichia pastoris and Hansenula polymorpha, which could lead to the inexpensive production of VP6 as a possible vaccine or drug delivery system.